ONE-LUNG VENTILATION PATIENTS: CLINICAL CONTEXT OF ADMINISTRATION OF DIFFERENT DOSES OF DEXMEDETOMIDINE: Dexmedetomidine in Patients Receiving One-lung Ventilation - Jiang, Hui; Kang, Yu; Ge, Chunlin; Zhang, Zhengying; Xie, Yan (Journal of Medical Biochemistry, 2021)
Background: To investigate the effects of different doses of dexmedetomidine on inflammatory response, oxidative stress, cerebral tissue oxygen saturation (SctO2) and intrapulmonary shunt in patients undergoing one-lung ventilation (OLV).Methods: Sixty patients undergoing open pulmonary lobectomy in our hospital from January 2016 to December 2017 were enrolled and randomly divided into high-dose dexmedetomidine group (group D1, 1 μg/kg, n=20), low-dose dexmedetomidine group (group D2, 0.5 μg/kg, n=20) and control group (group C, n=20). Then, arterial blood and internal jugular venous blood were taken before anesthesia induction (T0) and at 15 min after two-lung ventilation (T1) and 5 min (T2) and 30 min (T3) after OLV for later use. Next, the changes in hemodynamic parameters [mean arterial pressure (MAP), heart rate (HR) and pulse oxygen saturation (SpO2)] of patients were observed in each group. Enzyme-linked immunosorbent assay (ELISA) was carried out to detect serum inflammatory factors such as interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) and oxidative stress indicators [superoxide dismutase (SOD) and malondialdehyde (MDA)]. The changes in SctO2, arterial partial pressure of oxygen (PaO2) and intrapulmonary shunt Qs/Qt were observed. Additionally, the changes in lung function indicators like lung dynamic compliance (Cdyn) and airway peak pressure (Ppeak) were determined.Results: There were no statistically significant differences in the MAP, HR and SpO2 among three groups at each observation time point (P>0.05). At T2 and T3, the levels of serum IL-6, TNF-α and IL-8 were obviously decreased in group D1 and D2 compared with those in group C (P
Keywords: dexmedetomidine, one-lung ventilation, inflammatory response, oxidative stress, cerebral tissue oxygen saturation, intrapulmonary shunt